2016
DOI: 10.1002/hed.24520
|View full text |Cite
|
Sign up to set email alerts
|

Impaired vocal cord mobility in T2N0 glottic carcinoma: Suboptimal local control with Radiation alone

Abstract: Patients with glottic cancer with impaired vocal cord mobility (T2b) have a high rate of local failure with RT alone. The addition of concurrent chemotherapy should be considered for patients highly motivated toward larynx preservation and willing to accept the potential toxicity. © 2016 Wiley Periodicals, Inc. Head Neck 38: 1832-1836, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 25 publications
(43 reference statements)
0
19
0
Order By: Relevance
“…Patients with impaired vocal cord mobility are generally thought to do worse than those with intact vocal cord mobility 7,11,24,29,44‐46 . A meta‐analysis of 21 retrospective studies of patients with T2 glottic cancer showed impaired vocal cord mobility to be associated with a statistically significant decrease in LC 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with impaired vocal cord mobility are generally thought to do worse than those with intact vocal cord mobility 7,11,24,29,44‐46 . A meta‐analysis of 21 retrospective studies of patients with T2 glottic cancer showed impaired vocal cord mobility to be associated with a statistically significant decrease in LC 45 .…”
Section: Discussionmentioning
confidence: 99%
“…We suggest the subdivision of T2 glottic tumours into T2a (normal vocal cord mobility) and T2b (impaired mobility) should be included in the TNM classification. Synchronous platinum based chemotherapy with radical radiotherapy is now standard of care for T3 glottic cancers and has been shown to improve outcomes in T2 disease [ 33 35 ]. A retrospective review by Bhateja et al showed a trend towards inferior local control for T2b cancers treated with radiotherapy alone, compared to those with more advanced disease treated with chemoradiotherapy [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is difficult to compare these earlier results directly with our findings, the survival rates in our study tended to be favorable. Specifically, the nonsurgical treatments, including definitive RT and systemic CRT, yielded 5‐year local control (LC) or LRC rates of 62% to 65% and OS rates of 40 to 67% in patients with clinically advanced‐stage disease . Al‐Mamgani et al reported a 5‐year LRC rate of 64% in patients with advanced T2 (T2b) disease treated with definitive RT .…”
Section: Discussionmentioning
confidence: 99%
“…Al‐Mamgani et al reported a 5‐year LRC rate of 64% in patients with advanced T2 (T2b) disease treated with definitive RT . Additionally, Bhateja et al reported the 3‐year LRC rates of 73.2% and 91.5% in patients with (a) T2bN0 treated with RT or (b) T2b‐3N0‐2 treated with IV‐CRT, respectively, thereby demonstrating that CRT is a more favorable treatment for patients with T2b relative to RT alone . In a recent study of LP, Timme et al calculated a 2‐year LEDFS rate of 40% in patients with T3 disease treated with IV‐CRT .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation